Immediate Postpartum Contraception in Adolescents: Intention, Retention, and Repeat Pregnancies [35A]. (May 2017) - Cizek, Stephanie; Postlethwaite, Debbie; Alabaster, Amy; Greenfield, Isabel; Gupta, Pratima
Abstract : INTRODUCTION: Rapid repeat pregnancy (within 2 years) among young women poses serious health consequences. Long-acting reversible contraception (LARC) is safe and effective, and available to women immediately postpartum at our institution. Our primary aim was to compare the rapid repeat pregnancy rate for young women (aged 13-24 years) initiating LARC immediately postpartum versus initiating LARC within 8 weeks of delivery, and LARC versus other contraceptive methods. METHODS: A retrospective cohort study was conducted of 592 young women with a live birth from 2011-2013 within our healthcare system. Logistic regression models were used to determine the odds of rapid repeat pregnancy. RESULTS: Women using short-acting or no contraception had higher adjusted odds of rapid repeat pregnancy compared to those using LARC (aOR 2.9, 95% CI 1.5-6.0; and OR 3.2, 95% CI 1.6-7.0). Immediate postpartum LARC initiation had higher odds of rapid repeat pregnancy versus LARC initiation within 8 weeks (aOR 2.2, 95% CI 1.0-5.0). The LARC removal/expulsion rate within 2 years was 46% with immediate postpartum placement and 36% with 8 week placement. Women receiving immediate postpartum LARC were more likely to be under 18 years old, had higher gravidity, and received primarily subdermal implants. CONCLUSION: Overall, postpartum LARC use among young women resulted in decreased risk of rapid repeat pregnancy compared to short-acting or no contraception. However, because of early LARC removal and switching to short-acting or no method, young women initiating LARC immediately postpartum were more likely to experience a rapid repeat pregnancy than those initiating LARC around 6-8 weeks postpartum.